2023
DOI: 10.1111/jvh.13806
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive fibrosis markers for assessment of liver fibrosis in chronic hepatitis delta

Abstract: Assessment of liver fibrosis by non‐invasive means is clinically important. Studies in chronic hepatitis delta (CHD) are scarce. We evaluated the performance of eight serum fibrosis markers [fibrosis‐4 score (FIB‐4), aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio (AAR), age‐platelet index (API), AST‐to platelet‐ratio‐index (APRI), Goteborg University Cirrhosis Index (GUCI), Lok index, cirrhosis discriminant score (CDS) and Hui score] in CHD and chronic hepatitis B (CHB). Liver stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(95 reference statements)
2
6
0
Order By: Relevance
“…14,23 Similar to our data, TE was superior to serological NITs for the detection of liver cirrhosis, but cut-offs for the detection of liver cirrhosis differ. In the study by Kalkan et al 23 a lower cut-off of 10 kPa was identified to distinguish between cirrhosis and no cirrhosis. This is in contrast to our data proposing a higher cut-off for the identification of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…14,23 Similar to our data, TE was superior to serological NITs for the detection of liver cirrhosis, but cut-offs for the detection of liver cirrhosis differ. In the study by Kalkan et al 23 a lower cut-off of 10 kPa was identified to distinguish between cirrhosis and no cirrhosis. This is in contrast to our data proposing a higher cut-off for the identification of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 83%
“…TE in particular is used on a regular basis for initial staging of liver fibrosis and longitudinal monitoring of patients. For CHD, only two studies evaluated the diagnostic performance of TE 14,23 . Similar to our data, TE was superior to serological NITs for the detection of liver cirrhosis, but cut‐offs for the detection of liver cirrhosis differ.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3 There are some discrepancies regarding the optimal cut-off value for LSM to rule out cirrhosis (Table 1). Kalkan et al 5 proposed that a cut-off >10 Kpa (AUC: 0.95) is most effective for excluding cirrhosis, based on a patient cohort where a significant proportion were receiving interferon, which may affect LSM results. Da et al 6 suggested a cut-off (>14 Kpa), more similar to that reported by Sandmann, but only half the patients underwent liver biopsy.…”
Section: N V I T E D E D I T O R I a L Editorial: Liver Elastography ...mentioning
confidence: 99%
“…37,46 Assessment of liver stiffness by transient elastography (TE) may provide information on the fibrosis stage. TE appears to be the best non-invasive method for diagnosing significant fibrosis and cirrhosis 76,77 and similar to hepatitis B and hepatitis C they are better in ruling out cirrhosis than ruling in cirrhosis. However, suggested cut-offs for ruling in and ruling out cirrhosis have not been validated for CHD.…”
Section: S Econdary Endp Ointsmentioning
confidence: 99%